Correlation Among Body Composition Parameters and Long-Term Outcomes in Crohn's Disease After Anti-TNF Therapy - Ando, Katsuyoshi; Uehara, Kyoko; Sugiyama, Yuya; Kobayashi, Yu; Murakami, Yuki; Sato, Hiroki; Kunogi, Takehito; Sasaki, Takahiro; Takahashi, Keitaro; Ueno, Nobuhiro; Kashima, Shin; Moriichi, Kentaro; et al. (Frontiers in Nutrition, 2022)
Background: The impact of the body composition on the pathophysiology and clinical course of Crohn’s disease (CD) has not been fully elucidated. Aims: To reveal the correlations among body composition and long-term outcomes in CD after anti-TNF therapy. Methods: Ninety-one patients who received anti-TNF therapy as their first biologic treatment were enrolled. The skeletal muscle index (SMI), visceral and subcutaneous fat area (VFA, SFA), and the ratio of the VFA to SFA (mesenteric fat index; MFI) at the 3rd lumbar level were measured using CT imaging before the induction. The correlation among the body composition and outcomes were analyzed. Results: The 5-year cumulative secondary failure- and resection-free rates in patients with a low SMI were significantly lower than those with a high SMI. The 5-year cumulative secondary failure-free rate in the patients with low VF was significantly lower than that in those with high VF, and the 5-year cumulative resection-free rate in patients with a high MFI was significantly lower than that in those with a low MFI. Additionally, patients with low age and BMI had significantly higher cumulative secondary failure- and resection-free rates than those with high age and BMI, respectively. In the multivariate analyses, a low SMI was the only independent risk factor for secondary failure, while low age, a low SMI and high MFI were risk factors for bowel resection. Conclusion: The skeletal muscle mass and ratio of visceral to subcutaneous fat were suggested to be helpful indicators which reflected long-term outcome after anti-TNF therapy in CD.